Negative prognostic implications of non-sustained ventricular tachycardias in patients after prophylactic defibrillator implantation. (19th May 2022) - Sugawara, M; Kondo, Y; Ryuzaki, S; Yoshino, Y; Chiba, T; Kitagawa, M; Ito, R; Nakano, MI; Kajiyama, T; Nakano, MA; Kobayashi, Y
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Non-sustained ventricular tachycardia (NSVT) is frequent phenomenon in severe heart failure with reduced ejection fraction (HFrEF) patients, and causes any negative impacts on such patients. In the Japanese Circulation Society (JCS) and Japanese Heart Rhythm Society (JHRS) guidelines, NSVT is regarded as a major component of indication for implantable cardioverter defibrillator (ICD) implantation. However, the long-term prognostic significance of NSVT in severe HFrEF is incompletely resolved. Purpose: The aim of this study is to investigate the relation between prior NSVT episodes and major adverse cardiac events (MACEs) in HFrEF patients with an ICD as primary prophylaxis. Methods: We retrospectively analyzed our ICD database. Patients underwent primary prophylactic ICD implantation from 2007 to 2018 following ICD recommendation of JCS and JHRS guidelines. Patients met the criteria of receiving optimal medication therapy, symptomatic heart failure (New York Heart Association classification II or greater), and severe cardiac dysfunction (left ventricular ejection fraction (LVEF) is 35% or less). In the case of ischemic cardiomyopathy (ICM), implantation of ICD was done at least 40 days after myocardial infarction and at least 90 days after revascularization. Incidence of NSVT episodes were identified through daily electrocardiogram (ECG), Holter ECG or monitor ECG in the hospital. MACEs were defined as composite outcome of cardiovascular death, heart failure hospitalization, and appropriate ICD therapies. Results: A total of 148 consecutive patients were enrolled (male, 120 (81%); age, 62.1±11.8 years; LVEF, 23.0±5.86%; left ventricular end-diastolic diameter (LVDd), 67.6±9.26mm; paroxysmal or persistent atrial fibrillation (AF), 38 (26%); NSVT, 113 (76%); use of class III antiarrhythmic drugs, 48 (32%); ICM, 49 (33%); cardiac resynchronization therapy (CRT), 63 (43%)). The median follow-up duration was 58.5 months. As a result of comparison of the Kaplan-Meier curve between NSVT group (n=113) and non-NSVT group (n=35), cardiovascular death, heart failure hospitalization, and appropriate ICD therapy were not statistically different (Figures). Of those, MACEs were occurred to 60 patients (41%). The results of cox-regression analysis showed LVDd (HR: 1.07, 95% CI: 1.03-1.12, p<0.001), AF (HR: 2.88, 95% CI: 1.56-5.31, p<0.001) and ICM (HR: 1.78, 95% CI: 1.00-3.16, p=0.049) were the independent predictors of MACEs, however NSVT was not (Table). Conclusions: In this Japanese population, the long-term prognosis of severe HFrEF patients is considered to be comparable regardless of prior NSVT episodes. However, the incidence of MACEs in patients with severe HFrEF after ICD implantation was substantially high. ICM, left ventricle size, and atrial fibrillation were the potential risk factors for MACEs as the previous reports showed.